Study protocol - metabolic syndrome, vitamin D and bone status in South Asian women living in Auckland, New Zealand: A randomised, placebo-controlled, double-blind vitamin D intervention - von Hurst PR; Stonehouse W; Matthys C; Conlon C; Kruger MC; Coad J (BioMed Central Ltd part of Springer Science+Business Media, 2008)
Background The identification of the vitamin D receptor in the endocrine pancreas suggests a role for vitamin D in insulin secretion. There is also some limited evidence that vitamin D influences insulin resistance, and thus the early stages of the development of type 2 diabetes. Methods Eighty-four women of South Asian origin, living in Auckland, New Zealand, were randomised to receive either a supplement (4000IU 25(OH)D3 per day) or a placebo for 6 months. At baseline, all participants were vitamin D deficient (serum 25(OH)D3 <50 nmol/L), insulin resistant (HOMA-IR > 1.93) and/or hyperinsulinaemic, hyperglycemic or had clinical signs of dislipidaemia. Changes in HOMA-IR, lipids, parathyroid hormone, calcium and bone markers were monitored at 3 months and 6 months. Discussion This randomised, controlled trial will be the first to investigate the effect of vitamin D supplementation on insulin resistance in non-diabetic subjects. It will subsequently contribute to the growing body of evidence about the role of vitamin D in metabolic syndrome.Registered clinical. Trial registration Registered clinical trial – Registration No. ACTRN12607000642482
Keywords: Vitamin D; Metabolic syndrome; Insulin; Diabetes; Supplement; New Zealand; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321205 Nutrition and dietetics